2015
DOI: 10.1038/leu.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

KIT mutation analysis in mast cell neoplasms: recommendations of the European Competence Network on Mastocytosis

Abstract: Although acquired mutations in KIT are commonly detected in various categories of mastocytosis, the methodologies applied to detect and quantify the mutant type and -burden in various tissues and cells are poorly defined. We here propose a consensus on methodologies used to detect KIT mutations in patients with mastocytosis at diagnosis and in the follow up with sufficient precision and sensitivity in daily practice. In addition, we provide recommendations for sampling and storage of diagnostic material as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
237
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(249 citation statements)
references
References 89 publications
(187 reference statements)
1
237
1
10
Order By: Relevance
“…The cKITD816V mutation was detected in BM samples of 92.2% of 438 patients, consistent with previous reports [19]. Two D816V-negative patients had different cKIT mutations, D816H and K546K.…”
Section: Laboratory Featuressupporting
confidence: 91%
See 1 more Smart Citation
“…The cKITD816V mutation was detected in BM samples of 92.2% of 438 patients, consistent with previous reports [19]. Two D816V-negative patients had different cKIT mutations, D816H and K546K.…”
Section: Laboratory Featuressupporting
confidence: 91%
“…Conversely, the same methodologies were able to detect the mutation in 92% of BM samples, where mutation burden is higher, in line with others' experience. Therefore, as recently suggested, standardized and highly sensitive method of detection need to be devised and implemented to allow the convenient use of peripheral blood samples as a screening tools in patients suspected to have SM [19,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, virtually all aggressive systemic mastocytosis cases, as well as around one-fourth of indolent systemic mastocytosis patients, 6 present multilineage involvement of bone marrow cell compartments other than mast cells by the KIT mutation, 11,12,25,26 this being considered as the most powerful prognostic factor for disease progression among adult indolent systemic mastocytosis patients. 7,10,27 Recently, several groups 9,13,14 have confirmed the feasibility of detecting the KIT mutation in peripheral blood leukocytes; consequently, sensitive allele-specific oligonucleotide-qPCR approaches for peripheral blood detection of the KIT D816V mutation 13,28 have been included in recent consensus diagnostic algorithms 18 owing to the less invasive diagnostic approach in peripheral blood vs bone marrow. However, careful analysis of the literature shows discrepant results regarding both the frequency of systemic mastocytosis cases who are KIT D816V + in peripheral blood and the prognostic impact of the KIT D816V allele burden.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, such apparently discrepant results could be explained by the fact that different approaches were used to assess peripheral blood involvement by the KIT mutation (analysis on gDNA 9,13 vs cDNA 30 ), which therefore might have different sensitivities. Of note, no study has been reported so far in which paired peripheral blood and bone marrow samples had been analyzed in large series of systemic mastocytosis cases by two or more (highly sensitive) PCR methods, 28 to clarify such discrepancies. Furthermore, the precise relationship between the presence of KIT D816V + cells in peripheral blood and multilineage involvement of bone marrow hematopoiesis by the KIT mutation also remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation